Effects of unilateral tDCS over left prefrontal cortex on emotion regulation in depression: Evidence from concurrent functional magnetic resonance imaging. - van Dam, Wessel O.; Chrysikou, Evangelia G. (Cognitive, Affective & Behavioral Neuroscience, 2021)
Major depressive disorder (MDD) is the most common mood disorder and a primary cause of disability worldwide. MDD symptomatology entails disturbances in emotion regulation, namely one's ability to modify the intensity and duration of emotional reactions towards affective events. Transcranial direct current stimulation (tDCS) has emerged as a promising treatment for MDD. Yet, positive tDCS outcomes vary across studies, while the precise effects of the procedure for cortical excitability in MDD during emotion regulation remain largely unexplored. Here, we leveraged functional magnetic resonance imaging (fMRI)-compatible tDCS technology to examine the functional consequences of a unilateral anodal tDCS montage at 1.5 mA over left PFC (area F3; with the reference electrode over an extracephalic location) for brain activity during an emotion-regulation task in MDD patients and age-matched healthy control subjects. Our results revealed down-regulation of negative emotions in the right amygdala and visual cortex of healthy controls but not MDD patients prior to stimulation, the degree of which correlated with the magnitude of the participants' reappraisal scores. TDCS did not elicit significant changes in neural activation patterns for either group. These findings contribute to the literature on the pathophysiology of MDD by showing that a key disturbance in the disorder entails the ineffective down-regulation of activity not only within the amygdala, but also within visual cortical areas in response to negative information. Further, these results suggest that relative to bifrontal tDCS montages, unilateral stimulation of moderate intensity over left PFC may not be sufficient to elicit therapeutic effects for MDD.